Interaction of the DNA untwisting enzyme with the SV40 nucleoprotein complex. - Young, L S (1978)
The SV40 nucleoprotein complex which was isolated from infected CV-1 cells did not possess an active DNA untwisting enzyme. The superhelix density of the DNA in the chromatin complex was unchanged after treatment with purified rat liver DNA untwisting enzyme. However, in the presence of ethidium bromide (1 microgram/ml) the superhelix density was changed. Moreover, the nicked intermediate in the DNA untwisting reaction could be detected using the chromatin DNA as a substrate. These results show that the DNA in the SV40 chromatin which is accessible to the DNA untwisting enzyme is under no topological strain.